1992
DOI: 10.7164/antibiotics.45.1684
|View full text |Cite
|
Sign up to set email alerts
|

Asterric acid, a new endothelin binding inhibitor.

Abstract: Endothelin (ET) is a potent vasoconstrictor/ pressor peptide consisting of 21 amino acid residues isolated from the cultures of porcine aortic endothelial cells1}. Analysis of a human genomic library reveals three forms of ET (ET-1, ET-2 and ET-3) which have more than 70% homology with one another2). In various organs, high affinity and specific receptors for ET have been found3). They have been distinguished as receptors ETA and ETB4-5). ET-1 exhibits potent and long-lasting vasoconstrictive activity in vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 11 publications
0
35
1
Order By: Relevance
“…[2], and etc. Their reported bioactivities mainly focus on the endothelin (ET) binding inhibitory activities [1,8], with nearly no reports on cytotoxicity. Our study demonstrated for the first time that compound having diphenyl ether skeleton showed S phase inhibitory activity against K562 cell line.…”
Section: Cytotoxicities and Apoptosismentioning
confidence: 99%
See 2 more Smart Citations
“…[2], and etc. Their reported bioactivities mainly focus on the endothelin (ET) binding inhibitory activities [1,8], with nearly no reports on cytotoxicity. Our study demonstrated for the first time that compound having diphenyl ether skeleton showed S phase inhibitory activity against K562 cell line.…”
Section: Cytotoxicities and Apoptosismentioning
confidence: 99%
“…Asterric acid, possessing a diphenyl ether structure, was the first non-peptide endothelin (ET) binding inhibitor discovered [1,2]. In this paper we mainly report the isolation and structure determination of the new diphenyl ether (1), and its preliminary in vitro cytotoxicity against the K562 cell line.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 It is also an inhibitor of vascular endothelial growth factor (VEGF) and an endothelin receptor antagonist for the treatment of early stage idiopathic pulmonary fibrosis. 2,3 Although a number of asterric acid derivatives have been claimed to be useful in the treatment of myocardial infarction and renal insufficiency, 4 none of them has been reported to display antifungal activity.…”
mentioning
confidence: 99%
“…[4][5][6] Asterric acid has been described to be the first non-peptidic inhibitor of the endothelin receptor and dechlorodihydromaldoxin and dihydromaldoxin were found to selectively inhibit endothelin-1 binding to endothelin type A receptor with IC 50 values of 1.5 and 20 mM, respectively. 7,8 These compounds also inhibit the increase in intracellular Ca 2 þ concentration elicited by 1 nM endothelin-1 in A10 cells. 8 In addition, the asterric acid derivatives methyl asterric acid, methyl 3-chloroasterric acid and methyl 3,5-dichloroasterric acid exerted inhibitory activity on VEGF-induced capillary-like tube formation of human umbilical vein endothelial cells in vitro.…”
Section: Introductionmentioning
confidence: 99%